ANALISIS PERKEMBANGAN KONDISI FISIK DAYA TAHAN KARDIOVASKULAR, KEKUATAN OTOT LENGAN, DAN DAYA LEDAK OTOT TUNGKAI ATLET GULAT PORPROV JATIM KE-VI KABUPATEN TUBAN TAHUN 2019 LAKI-LAKI USIA 15-19 TAHUN - Jatmiko, Yongki; kumaat, noortje anita (Jurnal Kesehatan Olahraga, 2019)
Abstract Wrestling is a sport achievement that has the characteristic of a sport carried out by two people who drop or slam each other, master and turn their opponents on their backs. To become an accomplished wrestling athlete requires programmed technical and physical training to get optimal results in every match he faces. The purpose of this study was to know the physical development of cardiovascular endurance, arm muscle strength, and limb muscle explosive power of Tuban Wrestling Athletes after running a training program for 6 weeks.This research was based on the lack of knowledge about the development of the physical development of cardiovascular endurance, arm muscle strength, and the explosive power of limb muscle in Wrestling Athlete in Tuban Regency. This research method was used quantitative descriptive research design pre test and post test. The sample of this study was 12 Gulat Athletes in Tuban Regency, Men age 15-19 Years.The results showed the development of physical preparation: (1) The average cardiovascular endurance pre test results of 40, 414 ml / kg / minute to 41, 842 ml / kg / minute in the post test results were included in the category (less) and were spent at 3.53%. (2) The average pre test arm muscle strength test results were 42.33 times to 44, 25 times in the post test results included the category (medium) and increase by 4.53% . (3) Average pre test results explosive power of limb muscles 56, 42 cm to 60, 08 cm in the post test results and entered in the category (good) and increased by 6.48%. The conclusions of the whole test showed a significant development of the Cardiovascular Endurance Test, Arm Muscle Strength, and Leg Muscle Explosive Power. Keywords: Wrestling, Cardiovascular endurance, Arm muscle strength, Explosive strength of leg muscles